HtrA1 serine protease expression levels on age-related macular degeneration (AMD) patients in Yogyakarta - Supanji Supanji; Bahana Ilham Perdamaian Ayudha; Dianratri Anindita; Syifarahmah Anditta; Wahyu Widayanti Tri; Setya Wardhana Firman; Bayu Sasongko Muhammad; Eko Prayogo Mohammad; Nurini Agni Angela; Oka Chio (BIO Web of Conferences, 2020)
This research aims to investigate the HtrA1 serine protease circulating level of Age-related Macular Degeneration (AMD) patients in Yogyakarta, Indonesia. This study was conducted from January to August 2019 which included 38 AMD patients and 16 Non-AMD patients/controls (two groups). Baseline data and blood sample were collected. ELISA assay was used to measure the HtrA1 serine protease circulating level on both groups. SNP genotyping of rs10490924 was using restriction enzyme digestion. This study used The IBM SPSS® version 24 (Chicago, The USA) to determine the relationship between HtrA1 expression level and AMD incidence. AMD patients had higher HtrA1 serine protease level (35.31) than controls (30.08). However, there is no association found between HtrA1 serine protease level and AMD incidence (p-value>0.05, CI 95 %). However, HtrA1 serine protease did not associate positively to AMD incidence in Yogyakarta samples. Further analysis by grouping AMD patient based on the rs10490924 genotype show no statistical correlation between HTRA1 to the incidence of AMD. This result might be due to the lack of samples in the study groups. Future studies with larger number of samples are advised to better see the association between Htra1 serine protease level and AMD incidence.